Development of Psychomotor Functions in Preschool Children With Intellectual Disabilities Through The Means of Correctional Eurhythmics - Arkhipova, S.V. (2021)
Introduction: The article examines the problem of psychomotor development of preschool children with intellectual disabilities. The researched problem affects learning, upbringing, and socialization of children of said category and its resolution requires implication of not only traditional but also non-traditional tools including correctional eurhythmics. The goal of the study is to develop the organizational and methodical basis for the development of psychomotor functions in preschool children with intellectual disabilities through the means of musical rhythmic exercises.Materials and methods: The basis of the research is formed by general scientific cognition methods: analysis, synthesis, comparison, generalization; pedagogical experiment (ascertaining, forming, control), and empirical data analysis. The data acquired in the course of the study were processed in Excel via the methods of mathematical statistics. Results: The conducted study demonstrates a positive dynamic in the development of psychomotor functions in preschoolers with intellectual disabilities before and after conducting experimental work using the means of correctional eurhythmics. Discussion and conclusion: The collected data confirms that specially organized work using musical rhythmic games and exercises effectively contributes to the level of development of psychomotor functions in children with intellectual disabilities not only in the motor but also in the cognitive and emotional and volitional components. The prepared materials can be used by specialists and teachers of preschool education organizations interested in the development of psychomotor functions in preschool children with intellectual disabilities by the means of correctional eurhythmics.